A composite wave absorbing material and its application in variable frequency motor of electric vehicle
By doping graphene oxide and calcium stearate into FeSiCr-based material and carrying out corrosion modification treatment of NaCl salt solution, FeSiCr/GO/Y composite absorbing material was prepared, and the reflection of composite absorbing material in the prior art was solved. The problem that the peak loss cannot reach less than -10dB, achieving electromagnetic compatibility effect in electric vehicle frequency converter motors.
Patent Information
- Application Number
- CN202210629308.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The peak reflection loss of existing composite wave absorbing materials in the working frequency band of electric vehicle variable frequency motor cannot reach less than -10dB, which cannot meet the electromagnetic compatibility needs of electric vehicles.
FeSiCr is used as the base material, doped with graphene oxide and calcium stearate, and the NaCl salt solution corrosion modification treatment was used to prepare FeSiCr/GO/Y composite wave absorbing material with a thickness of 2.2mm, and its electromagnetic parameters are adjusted to The reflection loss is less than -10dB in the 1.7-2.8GHz frequency band.
In the application of electric vehicle frequency converter motors, the electromagnetic compatibility effect of composite wave absorbing materials is achieved, which meets the electromagnetic frequency band requirements of electric vehicles, and improves the wave absorbing performance of the material through corrosion modification.
Smart Images

Figure CN114929003B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of absorbing materials, and in particular to a FeSiCr / GO / Y composite absorbing material and its application in electric vehicles, and in particular to its application in electromagnetic compatibility of variable frequency motors of electric vehicles. Background Art
[0002] Traditional fuel vehicles are overly dependent on non-renewable petroleum resources and produce a large amount of harmful exhaust gas during use. They do not meet the current social environment development needs of energy conservation, emission reduction and dual-carbon economy. In this environment, new energy vehicles, especially electric vehicles, have developed rapidly.
[0003] The electrification of automobiles integrates the research and development and application of advanced materials with the manufacturing technology of high-precision components, and promotes the upgrading of battery, motor and electronic control technology. It is one of the most important application scenarios of the new generation of information technology, artificial intelligence, 5G, Internet of Things, etc. Moreover, the intelligent development of electric vehicles has become an important force to accelerate innovation in other industries.
[0004] The motor of an electric vehicle is a DC power supply (lithium battery) that works with high voltage frequency conversion after passing through an inverter. The operating frequency is related to the motor speed. The specific numerical range is technically confidential, but the maximum frequency will not exceed 2.5GHz, which belongs to the S band range. Since the motor that drives the wheels and weak current communication equipment such as on-board sensors and DC power supply equipment such as screens all use lithium batteries as the same power source, electromagnetic interference may be generated during operation, causing the electric vehicle to suddenly experience weak current or power failure while driving. In severe cases, it may cause sensor failure, causing the screen to go black or the brake transmission to fail, all of which will seriously endanger the personal safety of the driver. Therefore, in order to improve the electromagnetic compatibility characteristics between the strong and weak current components of electric vehicles, it is very necessary to provide absorbing materials that can work in a frequency band less than 2.5GHz.
[0005] Generally speaking, within the working frequency band, if the reflection loss reaches -10dB, it meets the application standard. The following table shows the electromagnetic wave attenuation standard:
[0006]
[0007] Magnetic metals have the advantages of high magnetic permeability, low strong magnetic loss and low cost, but due to their high electrical conductivity, their dielectric parameters are generally large and their electromagnetic matching characteristics are not high. Complex dielectric constant (ε′, ε″) and complex magnetic permeability (μ′, μ″) can be used to represent the specific electromagnetic properties of absorbing materials, that is, electromagnetic parameters. If you want the absorbing material to have good absorbing performance, adjusting the electromagnetic parameters ε and μ of the material is an effective means. If we only consider the absorption of electromagnetic waves by the absorbing material, on the basis of ensuring that ε′ and ε″ are as large as possible, the larger μ′ and μ″, the better. However, in practice, the complex dielectric constant ε is often not simply maximized as much as possible, but impedance matching must be taken into account, and specific analysis must be made based on the differences in the electromagnetic properties of different materials: on the one hand, it is necessary to consider that the absorbing material has an attenuation characteristic, that is, to maximize the attenuation and absorption of the electromagnetic waves that have entered the material, so as to achieve the purpose of avoiding the incident electromagnetic wave from being reflected again; on the other hand, impedance matching must also be considered to avoid the incident electromagnetic wave being directly reflected back at the incident interface.
[0008] Coupling agents can improve the compatibility of absorbing materials and rubber matrix, changing the surface of absorbing materials from hydrophilic to hydrophobic. Moreover, coupling agents can effectively reduce the conductivity between particles. Therefore, it is a relatively simple and inexpensive method to modify the surface of absorbing materials through coupling agents to improve their impedance matching characteristics.
[0009] As a typical two-dimensional crystal, graphene has the characteristics of low resistivity, good thermal stability, fast electron migration and high electrical conductivity. Due to certain defects on the graphene surface, multiple graphene sheets are easily stacked, eventually forming a multilayer composite structure, which helps to lose electromagnetic waves entering the material because the propagation distance and number of reflections of the incident electromagnetic waves in the multilayer composite structure will be greatly increased. Graphene is also commonly used for doping to prepare composite absorbing materials, because the addition of graphene can often effectively improve the corrosion resistance of the coating. Natural graphite powder can obtain graphene oxide after a series of chemical treatments. There are various oxygen-containing functional groups (C=O, CO, OH) in graphene oxide, which leads to the frequent use of graphene oxide doping to prepare composite materials with various electromagnetic properties.
[0010] Gao Xin's master's thesis - Research on the Absorption Characteristics of Magnetic Metals and Their Composite Absorbing Materials under Corrosion Behavior proposed using magnetic metals as the basis, doping with composite coupling agents and graphene oxide, and using high-energy ball milling to prepare a series of magnetic metal composite absorbing materials. The corrosion tests were carried out under salt corrosion and phosphoric acid solution respectively, and the composite material was subjected to static immersion corrosion test. The microstructure and electromagnetic parameters of the composite absorbing samples before and after corrosion were compared. It was found that when the thickness was 1.5mm, the addition of the composite coupling agent significantly enhanced the minimum reflection loss of the composite material after corrosion; the addition of graphene oxide helped to improve the absorption bandwidth after salt solution corrosion; however, the paper focused on the change trend of the absorption performance of the composite material before and after corrosion, that is, after the composite absorbing material was corroded, the change in absorption performance was smaller than that of the uncomposite absorbing material, or the composite absorbing material had better corrosion resistance; it was unclear whether the corrosion process could improve the absorption performance of the composite absorbing material, and the loss peak of the material appeared in the 3-4GHz frequency band, within which the minimum reflection loss of the composite material under salt solution corrosion could reach less than -10dB; and it did not roughly correspond to the operating frequency band of electric vehicle motors (≤2.5GHz).
[0011] Therefore, in order to better promote the long-term progress of electric energy, it is necessary to further explore the development of composite absorbing materials based on material properties, so as to effectively regulate the frequency band of the reflection loss peak of the composite material to meet the development needs of electric vehicles and related fields. Summary of the invention
[0012] The purpose of the present invention is to solve the problems existing in the prior art. By adjusting the parameters, the frequency band regulation of the reflection loss peak of the composite material is completed, so that the prepared composite absorbing material can be used in the variable frequency motor of electric vehicles and has electromagnetic compatibility effect.
[0013] The technical solution disclosed in the present invention is: an application of a composite absorbing material on a variable frequency motor of an electric vehicle. The composite absorbing material is FeSiCr / GO / Y, which is prepared by doping graphene oxide (GO) and a coupling agent-calcium stearate (Y) with a metal soft magnetic material FeSiCr as a base. The material thickness is 2.2 mm, and the frequency band when the reflection loss RL is less than -10 dB is between 1.7-2.8 GHz. The addition amount of graphene oxide and calcium stearate in the composite absorbing material is 0-1.5% of the mass of FeSiCr, and after compounding, the composite is subjected to corrosion modification treatment by a NaCl salt solution. The specific preparation process is as follows:
[0014] (1) In order to remove low melting point impurities and surface water vapor on the surface of the FeSiCr alloy powder raw material, the FeSiCr raw material is placed in a vacuum furnace and preheated at a low temperature;
[0015] (2) placing FeSiCr powder, graphene oxide, calcium stearate and bearing steel balls for ball milling into a ball milling jar;
[0016] (3) Add anhydrous ethanol to the ball mill. The anhydrous ethanol should be able to completely immerse the raw materials. Use a glass rod to Break Stirring straight arrive Mix evenly, seal and store, and put into a vibrating ball mill for ball milling;
[0017] (4) After the ball milling is completed, the obtained slurry is dried in vacuum to obtain the FeSiCr / GO / Y composite absorbing material;
[0018] (5) The FeSiCr / GO / Y composite absorber obtained in the previous step is placed in a NaCl solution for corrosion treatment. After the corrosion treatment is completed, the corrosion sample is post-treated to obtain a surface corrosion-modified FeSiCr / GO / Y composite absorber.
[0019] Furthermore, in step (1), the low-temperature preheating temperature is 100-200° C., and the preheating time is 1-2 hours.
[0020] Furthermore, in step (2), the mass ratio of the balls is 1:(8-10).
[0021] Furthermore, in step (2), the diameters of the added bearing steel balls for ball milling are 6 mm, 8 mm, and 12 mm, and the weight ratio of the three diameters of the bearing steel balls is 1:1:1.
[0022] Furthermore, in step (3), after adding anhydrous ethanol to the ball mill, the anhydrous ethanol is 1-2 cm higher than the surface of the material balls, the frequency of the oscillating ball mill is 10-20 Hz, and the oscillating ball milling time is 1-2 h.
[0023] Furthermore, in step (4), the vacuum drying temperature is 45-55°C, and the drying time is 2-3h.
[0024] Furthermore, in step (5), the mass concentration of the NaCl solution is 3-4%, and the FeSiCr / GO / Y composite absorbing material is allowed to stand in the NaCl solution for 18-24 hours.
[0025] Furthermore, in step (5), when the corrosion treatment is performed, the FeSiCr / GO / Y composite absorbing material is placed in a NaCl solution, and then stirred several times with a glass rod until it is relatively uniform. After the corrosion environment is sealed, small holes are opened to allow air to flow smoothly. After standing for a while, the upper clear liquid is filtered out to leave the corrosion sample.
[0026] Furthermore, in step (5), the post-treatment process is to first wash and filter the corrosion sample several times with anhydrous alcohol, and then put the washed sample into a vacuum drying oven and dry it at 45-55°C for 1-2h.
[0027] The beneficial effects of the present invention are:
[0028] 1. After the thickness of the FeSiCr / GO / Y composite absorbing material prepared in this application is controlled at 2.2 mm, the frequency band when the reflection loss RL of the material is less than -10 dB is 1.9-2.8 GHz, that is, the reflection loss peak value in the motor working frequency band (≤2.5 GHz) basically reaches a level less than -10 dB, which basically meets the requirements of the electromagnetic frequency band for the application of variable frequency motors in electric vehicles, which will be conducive to the long-term progress of electric vehicles and related fields;
[0029] 2. This application improves the absorbing performance of the composite absorbing material through corrosion modification, so that the prepared composite absorbing material can be used in the variable frequency motor of electric vehicles and has electromagnetic compatibility effect;
[0030] 3. The present invention discloses a composite absorbing material, which not only utilizes a corrosion process to modify the surface of the material, but also obtains the properties of the composite material by doping GO and Y. The composite absorbing material prepared in this way has both a certain shape isotropy and good absorbing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 It is a flow chart of the preparation method of FeSiCr / GO / Y composite absorbing material used in variable frequency motors of electric vehicles;
[0032] Figure 2A is a reflection loss diagram of the composite absorbing material prepared in Example 1 (thickness = 2.2 mm);
[0033] Figure 2B is a SEM photograph of the composite absorbing material prepared in Example 1;
[0034] Figure 2C is a scanning diagram of the energy spectrum of the composite material obtained in Example 1;
[0035] Figure 3A is a reflection loss diagram of the composite absorbing material prepared in Example 2 (thickness = 2.2 mm);
[0036] Figure 3B is a SEM photograph of the composite absorbing material prepared in Example 2;
[0037] Figure 4A is a reflection loss diagram of the composite absorbing material prepared in Example 3 (thickness = 2.2 mm);
[0038] Figure 4B is a SEM photograph of the composite absorbing material prepared in Example 3;
[0039] Figure 5A is a reflection loss graph of the composite absorbing material prepared in Comparative Example 1 (thickness = 2.2 mm);
[0040] Figure 5B is a SEM photograph of the composite absorbing material prepared in Comparative Example 1;
[0041] Fig. 6A is a reflection loss diagram of the composite absorbing material prepared in Comparative Example 2 (thickness = 2.2 mm);
[0042] Figure 6B This is a SEM photo of the composite absorbing material prepared in Comparative Example 2;
[0043] Figure 7 1 is a real part diagram of the complex dielectric constant of the composite absorbing materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 (S1-Example 1, S2-Example 2, S3-Example 3, B1-Comparative Example 1, B2-Comparative Example 2);
[0044] Figure 8 It is a graph of the imaginary part of the complex dielectric constant of the composite absorbing materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 (S1-Example 1, S2-Example 2, S3-Example 3, B1-Comparative Example 1, B2-Comparative Example 2);
[0045] Fig. 9 1 is a real part diagram of complex magnetic permeability of composite absorbing materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 (S1-Example 1, S2-Example 2, S3-Example 3, B1-Comparative Example 1, B2-Comparative Example 2);
[0046] Fig.10 It is a graph of the imaginary part of the complex magnetic permeability of the composite absorbing materials prepared in Examples 1, 2, 3 and Comparative Examples 1 and 2 (S1 - Example 1, S2 - Example 2, S3 - Example 3, B1 - Comparative Example 1, B2 - Comparative Example 2). DETAILED DESCRIPTION
[0047] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all belong to the scope of the present invention.
[0048] Example 1: Preparation of FeSiCr / GO / Y composite absorbing material for electric vehicle variable frequency motor Take 200g FeSiCr powder raw material, preheat it at 100℃ for 2h, add 2g calcium stearate (Y), 2g GO and bearing steel ball, then add 250mL anhydrous ethanol to immerse the above raw materials, stir them evenly with a glass rod, seal and store them, and put them into a oscillating ball mill for 1h; ball milling changes the morphology of FeSiCr powder particles into a flaky structure with a certain aspect ratio, so that the FeSiCr raw material, calcium stearate and doped GO are evenly mixed. The ball-milled FeSiCr / GO / Y slurry is placed in a vacuum drying oven and dried at 50℃ for 2h to obtain a FeSiCr / GO / Y composite absorbing material. The dried composite material was immersed in a 3.5% by mass NaCl solution for 20 hours for corrosion treatment. After the corrosion was completed, the supernatant was filtered out to leave the corrosion powder. The corrosion powder was rinsed with anhydrous alcohol for 3 times. The slurry after washing was placed in a vacuum drying oven and vacuum dried at 50°C for 2 hours to obtain the FeSiCr / GO / Y composite absorbing material after NaCl corrosion modification treatment.
[0049] The electromagnetic parameters (complex dielectric constant, complex magnetic permeability) of the composite absorbing material are measured by a vector network analyzer, and then the reflection loss curve with frequency when the coating thickness is 2.2 mm is calculated according to the electromagnetic field transmission line theory, as shown in the figure. Figure 2A As shown, it is found that the frequency band when the reflection loss RL is less than -10dB is 1.93-2.78GHz, and the bandwidth is 0.85GHz, which basically fits the electromagnetic frequency band of the variable frequency motor application of electric vehicles.
[0050] Figure 2B is a SEM photograph of the composite material obtained in this embodiment. The picture shows that the microstructure of the obtained material is a lamellar structure, which is conducive to breaking through the Snoke limit and has a larger complex magnetic permeability.
[0051] Figure 2C It is a spectrum scanning diagram of the composite material prepared in this embodiment. The FeSiCr / GO / Y sample contains carbon element, indicating that the surface fine particles in its SEM image are GO.
[0052] Example 2: Preparation of FeSiCr / GO composite wave absorbing material for electric vehicle variable frequency motor
[0053] Take 200g FeSiCr powder raw material, preheat it at 100℃ for 2h, add 2g GO and bearing steel ball, then add 250mL anhydrous ethanol to immerse the above raw materials, stir it evenly with a glass rod, seal it and store it, put it into a swing ball mill for 1h; ball milling changes the morphology of FeSiCr powder particles into a lamellar structure with a certain aspect ratio, so that the FeSiCr raw material and doped GO are evenly mixed. The ball-milled FeSiCr / GO slurry is placed in a vacuum drying oven and dried at 50℃ for 2h to obtain a FeSiCr / GO composite absorbing material. The dried composite material is immersed in a NaCl solution with a mass ratio of 3.5% for 20h for corrosion treatment. After the corrosion is completed, the supernatant is filtered out to leave the corrosion powder. The corrosion powder is rinsed with anhydrous alcohol for 3 times. The slurry after cleaning is placed in a vacuum drying oven and vacuum dried at 50℃ for 2h to obtain a FeSiCr / GO composite absorbing material after NaCl corrosion modification.
[0054] The electromagnetic parameters (complex dielectric constant, complex magnetic permeability) of the composite absorbing material are measured by a vector network analyzer, and then the reflection loss curve with frequency when the coating thickness is 2.2 mm is calculated according to the electromagnetic field transmission line theory, as shown in the figure. Figure 3A As shown, it is found that the frequency band when the reflection loss RL is less than -10dB is 1.77-1.95GHz, and the bandwidth is 0.18GHz, which is completely consistent with the electromagnetic frequency band of electric vehicle variable frequency motor application.
[0055] Figure 3B : is a SEM photograph of the composite material prepared in this example, and the picture shows that the microstructure is still a lamellar structure.
[0056] Example 3: Preparation of FeSiCr / Y composite wave absorbing material for electric vehicle variable frequency motor
[0057] Take 200g FeSiCr powder raw material, preheat it at 100℃ for 2h, add 2g calcium stearate (Y) and bearing steel ball, then add 250mL anhydrous ethanol to immerse the above raw materials, stir it evenly with a glass rod, seal it and store it, put it into a swing ball mill for 1h; ball milling changes the morphology of FeSiCr powder particles into a lamellar structure with a certain aspect ratio, so that the FeSiCr raw material and Y are evenly mixed. The FeSiCr / Y slurry after ball milling is placed in a vacuum drying oven and dried at 50℃ for 2h to obtain a FeSiCr / Y composite absorbing material. The dried composite material is immersed in a NaCl solution with a mass ratio of 3.5% for 20h for corrosion treatment. After the corrosion is completed, the supernatant is filtered out to leave the corrosion powder. The corrosion powder is rinsed with anhydrous alcohol for 3 times. The slurry after cleaning is placed in a vacuum drying oven and vacuum dried at 50℃ for 2h to obtain a FeSiCr / Y composite absorbing material after NaCl corrosion modification.
[0058] The electromagnetic parameters (complex dielectric constant, complex magnetic permeability) of the composite absorbing material are measured by a vector network analyzer, and then the reflection loss curve with frequency when the coating thickness is 2.2 mm is calculated according to the electromagnetic field transmission line theory, as shown in the figure. Figure 4A As shown, it is found that the frequency band when the reflection loss RL is less than -10dB is 1.73-2.57GHz, and the bandwidth is 0.84GHz, which is basically in line with the electromagnetic frequency band of the variable frequency motor application of electric vehicles.
[0059] Figure 4B : is a SEM photograph of the composite material prepared in this example, and the picture shows that the microstructure is still a lamellar structure.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that FeSiCr is not doped with GO or Y, nor is it treated with NaCl solution corrosion, and the other processes are the same. The curve of reflection loss versus frequency when the coating thickness is 2.2 mm is calculated according to the line transmission theory, as shown in FIG. Figure 5A As shown in the figure, it is found that the frequency band when the reflection loss is RL < -10dB is 2.86-4.29GHz, the bandwidth is 1.41GHz, and the frequency band range of -10dB is > 2.5GHz, which does not meet the electromagnetic frequency band requirements for the application of variable frequency motors in electric vehicles.
[0062] Figure 5B The SEM photo of Example 1 shows that the microstructure is still a flake structure, but the size distribution of FeSiCr is uneven, with a diameter of 10-50 μm. Figure 2B ) Compared with the sample prepared in comparative example 1, the microscopic size is reduced, indicating that the addition of GO and Y helps the uniformity of ball milling, but the surface of the sample is no longer smooth and some small particles appear. After energy spectrum analysis, it was found that ( Figure 2C ), the FeSiCr / GO / Y sample contains carbon, indicating that the fine surface particles in its SEM image are GO.
[0063] Comparative Example 2
[0064] The difference from Example 1 is that FeSiCr is not doped with GO or Y, and the other steps are the same (i.e., it is also treated with NaCl solution corrosion). According to the line transmission theory, the reflection loss curve of the coating thickness of 2.2 mm is calculated as a function of frequency. As shown in FIG6 , the frequency band when RL <-10 dB is 2.23-2.79 GHz, the bandwidth is 0.56 GHz, and the lower limit of the frequency band is close to 2.5 GHz. As we all know, engineering parameters must have a margin, so it cannot meet the electromagnetic frequency band requirements of electric vehicle variable frequency motor applications.
[0065] Figure 6B The SEM photo of Example 2 shows that the microstructure is still a flaky structure, but after the corrosion treatment, there is an obvious agglomeration phenomenon; while the sample prepared in Example 1 can be seen ( Figure 2B ), there is no obvious agglomeration phenomenon, indicating that the addition of coupling agent calcium stearate can not only improve the uniformity of ball milling, but also effectively reduce the agglomeration phenomenon.
[0066] Figure 7 , 8 , 9, and 10 are the electromagnetic parameter data of Examples 1-3 and Comparative Examples 1-2 (the reflection loss RL is directly determined by the complex electromagnetic parameters μ=μ′-jμ″, ε=ε′-jε″), and the complete matching condition is μ=ε. The closer the values of the two parameters are, the better. However, since the dielectric parameter of the metal is much larger than the magnetic permeability (because the metal is a good conductor), the key to matching the metal absorbing material is to reduce the complex dielectric parameter ε. It is worth noting that since it is necessary to work in the low-frequency S-band (≤2.5GHz), the dielectric parameter cannot be too small. If the dielectric parameter is too small, the reflection loss peak will appear at high frequency (such as Comparative Example 1), and the reflection loss is affected by the thickness, so it is necessary to comprehensively consider parameter control to achieve the desired absorbing performance.
[0067] Summary: All the absorbers prepared in the examples are in a flaky structure, which is conducive to improving the Snoek limit and thus obtaining a larger magnetic loss. However, the flaking of the powder will increase its interface polarization, thereby increasing the dielectric constant, which is not conducive to the impedance matching of the absorber. After GO and Y are added alone or in combination, the surface modification of the NaCl solution can effectively inhibit the interface polarization, thereby improving the impedance matching. After the coating thickness is adjusted accordingly, the minimum reflection loss (RL) can be obtained in the frequency range of ≤2.5GHz. min ) is less than -10dB, which not only has excellent loss performance but also is suitable for the electromagnetic frequency band requirements of electric vehicle variable frequency motor applications.
[0068] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. An application of a composite wave absorbing material in a variable frequency motor of an electric vehicle, characterized in that: The composite absorbing material is FeSiCr / GO / Y, which is prepared by doping graphene oxide and coupling agent-calcium stearate with metal soft magnetic material FeSiCr as the base, and the material thickness is 2.2mm. The frequency band when the reflection loss RL is less than -10dB is between 1.7-2.8GHz. The doping amount of graphene oxide and calcium stearate in the composite absorbing material is 0-1.5% of the mass of FeSiCr, and after the composite, it is corroded and modified by NaCl salt solution. The specific preparation process is as follows: (1) Place the FeSiCr raw material into a vacuum furnace and preheat at low temperature; (2) placing FeSiCr, graphene oxide, calcium stearate and bearing steel balls for ball milling into a ball milling jar; (3) adding anhydrous ethanol to the ball mill, stirring and mixing, sealing and storing, and placing in a oscillating ball mill for ball milling; (4) After the ball milling is completed, the slurry is dried in vacuum to obtain the FeSiCr / GO / Y composite absorbing material; (5) The FeSiCr / GO / Y composite absorber obtained in the previous step is placed in a NaCl solution for corrosion treatment. After the corrosion treatment is completed, the corrosion sample is post-treated to obtain a surface corrosion-modified FeSiCr / GO / Y composite absorber.
2. The application of a composite absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (1), the low-temperature preheating temperature is 100-200° C., and the preheating time is 1-2 hours.
3. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (2), the mass ratio of the balls is 1:(8-10).
4. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (2), the diameters of the bearing steel balls added for ball milling are 6 mm, 8 mm, and 12 mm, respectively, and the weight ratio of the three diameters of the bearing steel balls is 1:1:
1.
5. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (3), after adding anhydrous ethanol to the ball mill, the liquid level of anhydrous ethanol is 1-2 cm higher than the surface of the material balls, the frequency of the oscillating ball mill is 10-20 Hz, and the oscillating ball milling time is 1-2 h.
6. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (4), the vacuum drying temperature is 45-55° C. and the drying time is 2-3 h.
7. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (5), the mass concentration of the NaCl solution is 3-4%, and the FeSiCr / GO / Y composite absorbing material is allowed to stand in the NaCl solution for 18-24 hours.
8. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (5), when the corrosion treatment is performed, the FeSiCr / GO / Y composite absorbing material is placed in a NaCl solution, stirred evenly, the corrosion environment is sealed but small holes are opened to allow air circulation, and after standing for a while, the upper clear liquid is filtered out to leave the corrosion sample.
9. The application of a composite wave absorbing material in a variable frequency motor of an electric vehicle as claimed in claim 1, characterized in that: In step (5), the post-treatment process is to first wash and filter the corrosion sample several times with anhydrous alcohol, and then put the washed sample into a vacuum drying oven and dry it at 45-55°C for 1-2h.
Citation Information
Patent Citations
Spherical FeSiCr magnetic nanometer wave absorbing material and preparation method thereof
CN109811268A
Preparation method of corrosion-resistant carbonyl iron / graphene composite wave absorbing material for 5G mobile communication frequency bands
CN109897597A
